High Performance Computing Clusters Design & Analysis Using Red Hat Enterprise Linux - Atiqur Rahman (Institute of Advanced Engineering and Science, 2015)
The purpose of this paper was to configure a cluster computing system to improve performance over that of a single computer, while typically being much more cost-effective than single computers of comparable speed. High performance computing more and more issued in all kinds of fields. But, for the common user, there are several questions on implementing the process of competing on the specialized clusters: such as expense high, management difficulty and operation complex and so on. To overcome these problems, this article designs and realizes the high performance computing environment based on Linux cluster after studying the key technology of cluster and parallel computing. Finally, the performance of system environment is tested by interactive version of CPI algorithm. Before discussion on HPC the cluster computing system with its classification, the advantages and application of clustering system will also be discussed here. DOI: http://dx.doi.org/10.11591/telkomnika.v14i3.7798